Direct application of the INNO-LiPA Rif.TB line-probe assay for rapid identification of Mycobacterium tuberculosis complex strains and detection of rifampin resistance in 360 Mycobacterium tuberculosis complex strains and detection of rifampin resistance in 360 smear-positive respiratory specimens from an area of high incidence of multidrug-resistant tuberculosis - Viveiros, M (2005)
The INNO-LiPA Rif.TB assay for the identification of Mycobacterium tuberculosis complex strains and the detection of rifampin (RIF) resistance has been evaluated with 360 smear-positive respiratory specimens from an area of high incidence of multidrug-resistant tuberculosis (MDR-TB). The sensitivity when compared to conventional identification/culture methods was 82.2%, and the specificity was 66.7%; the sensitivity and specificity were 100.0% and 96.9%, respectively, for the detection of RIF resistance. This assay has the potential to provide rapid information that is essential for the effective management of MDR-TB.